Sejarah Perkembangan Metode Pengajaran Bahasa Arab di Indonesia - Rifqi, Ahmad; Promadi, Promadi (STAI Ali bin Abi Thalib Surabaya, 2025)
The development of Arabic teaching methods in Indonesia is very necessary to know about how the history of the development of these methods. The purpose of this study is to find out how Arabic language teaching developed in Indonesia, how the explanation of the entry of Arabic into Indonesia, and how Arabic language teaching developed in Indonesia. Allah chose Arabic to speak with His servants, the development of Arabic is a reflection of the history, culture, and identity of Arab society and the Islamic world. Emphasis is placed on the evolution of Arabic language teaching methods in Indonesia, which includes an in-depth analysis of the changes from the verbalistic system to the electic system. This research also provides insight into the relationship between Arabic, Islam, and the identity of Arab society and the Islamic world, which has not been widely discussed in previous literature. In addition, this research uses a qualitative historiographic approach to reconstruct the development of Arabic in Indonesia, which provides a new perspective in this study. The data in the research on the development of Arabic teaching methods in Indonesia by using documentation, namely collecting data consisting of books, scientific journals, ebooks, and articles on the website. After all collected, then read and recorded to be processed as research material. The researcher found that the development of Arabic teaching methods in Indonesia is not something relatively simple, as it seems today, or like something that is very easy for us to do. This is due to the changing times that are increasingly developing, which means that teaching methods are always changing. With the changing times, Arabic teaching methods in Indonesia at this time have developed rapidly since its arrival in the 7th century until the 20th century.